Characterization of four Latin American families confirms previous findings and reveals novel features of acid‐labile subunit deficiency. (14th June 2017) - Scaglia, Paula A.; Keselman, Ana C.; Braslavsky, Débora; Martucci, Lucía C.; Karabatas, Liliana M.; Domené, Sabina; Gutiérrez, Mariana L.; Ballerini, María G.; Ropelato, María G.; Spinola‐Castro, Angela; Siviero‐Miachon, Adriana A.; Tartuci, Juliana Saito; et al.
Summary: Objective: Acid‐labile subunit deficiency (ACLSD), caused by inactivating mutations in both IGFALS gene alleles, is characterized by marked reduction in IGF‐I and IGFBP‐3 levels associated with mild growth retardation. The aim of this study was to expand the known phenotype and genetic characteristics of ACLSD by reporting data from four index cases and their families. Design: Auxological data, biochemical and genetic studies were performed in four children diagnosed with ACLSD and all available relatives. Methods: Serum levels of IGF‐I, IGFBP‐3, acid‐labile subunit (ALS), and in vitro ternary complex formation (ivTCF) were determined. After sequencing the IGFALS gene, pathogenicity of novel identified variants was evaluated by in vitro expression in transfected Chinese hamster ovarian (CHO) cells. ALS protein was detected in patients′ sera and CHO cells conditioned media and lysates by Western immunoblot (WIB). Results: Four index cases and four relatives were diagnosed with ACLSD. The following variants were found: p.Glu35Glyfs*17, p.Glu35Lysfs*87, p.Leu213Phe, p.Asn276Ser, p.Leu409Phe, p.Ala475Val and p.Ser490Trp. ACLSD patients presented low IGF‐I and low or undetectable levels of IGFBP‐3 and ALS. Seven out of 8 patients did not form ivTCF. Conclusions: This study confirms previous findings in ACLSD, such as the low IGF‐I and a more severe reduction in IGFBP‐3 levels, and a gene dosage effect observed in heterozygous carriers (HC). In addition, father‐to‐son transmission (father compound heterozygous and mother HC), preservation of male fertility, and marginal ALS expression with potential involvement in preserved responsiveness to rhGH treatment, are all novel aspects, not previously reported in this condition.